Institutions governing the use of forest products: woodcraft commercialisation in southern Zimbabwe - Braedt, O.; Schroder, J.M. (2003)
The production and sales of woodcarvings rose substantially during the 1990s in Zimbabwe. Potential conflict between informal groups selling forest commodities and institutions that control the use of forest products is inherent in this fast growing sector. The aim of this study was to identify organizations, stakeholders, and institutions associated with the control and management of tree use on communal lands, to assess how familiar people are with these institutions, and to establish the level of enforcement of the various rules. Formal institutions governing natural resource use are part of state organizations that have published and codified control mechanisms in place. Informal institutions were considered to be traditional leadership structures. In rural areas, knowledge of the official/codified control mechanisms was practically absent, being limited to the few persons in charge of the execution of the legal provisions. Effective control and prosecution of offenders under either theformal or informal system was rare. In practice an open-access situation without any form of controls on tree use for carvings was apparent, and a degree of confusion over who controls forest product use was prevalent.